Trends in taxonomy of Triatomini (Hemiptera, Reduviidae, Triatominae): reproductive compatibility reinforces the synonymization of Meccus Stål, 1859 with Triatoma Laporte, 1832 - Cesaretto, Natália Regina (Parasit Vectors, 2021)
BACKGROUND: Meccus' taxonomy has been quite complex since the first species of this genus was described by Burmeister in 1835 as Conorhinus phyllosoma. In 1859 the species was transferred to the genus Meccus and in 1930 to Triatoma. However, in the twentieth century, the Meccus genus was revalidated (alteration corroborated by molecular studies) and, in the twenty-first century, through a comprehensive study including more sophisticated phylogenetic reconstruction methods, Meccus was again synonymous with Triatoma. Events of natural hybridization with production of fertile offspring have already been reported among sympatric species of the T. phyllosoma subcomplex, and experimental crosses demonstrated reproductive viability among practically all species of the T. phyllosoma subcomplex that were considered as belonging to the genus Meccus, as well as between these species and species of Triatoma. Based on the above, we carried out experimental crosses between T. longipennis (considered M. longipennis in some literature) and T. mopan (always considered as belonging to Triatoma) to evaluate the reproductive compatibility between species of the T. phyllosoma complex. In addition, we have grouped our results with information from the literature regarding crosses between species that were grouped in the genus Meccus with Triatoma, in order to discuss the importance of experimental crosses to confirm the generic reorganization of species. RESULTS: The crosses between T. mopan female and T. longipennis male resulted in viable offspring. The hatching of hybrids, even if only in one direction and/or at low frequency, demonstrates reproductive compatibility and homeology between the genomes of the parents. CONCLUSION: Considering that intergeneric crosses usually do not result in viable offspring in Triatominae, the reproductive compatibility observed between the T. phyllosoma subcomplex species considered in the Meccus genus with species of the Triatoma genus shows that there is “intergeneric” genomic compatibility, which corroborates the generic reorganization of Meccus in Triatoma. GRAPHIC ABSTRACT: [Image: see text]